THE EFFECT OF CRYOTHERAPY AND ACUPUNCTURE ON PHYSICAL PERFORMANCE, BLOOD LACTATE, AND MUSCLE SORENESS AFTER FUTSAL-SPECIFIC INTERMITTEN SHUTTLE PROTOCOL IN COLLEGIATE FUTSAL PLAYERS - Harun
Futsal is a high intensity-intermittent sport and need a high performance skills. It is often played in consecutive days and have short recovery. An optimal recovery is strongly required after repeated intense physical exertion. The study is aimed to compared the effects of cryotherapy and acupuncture on physical performance, blood lactate and muscle soreness in collegiate futsal players after Futsal-Specific Intermittent Shuttle Protocol (FISP) exercise. Experimental counterbalance crossover is used in this study. Eleven collegiate futsal players participated in 3 weeks and received a different recovery strategy in different week. During week 1, all players completed all passive recovery, during week 2 all players received cryotherapy and all players received acupuncture in week 3. Countermovement jump (CMJ), sprint 20 m, blood lactate, and muscle soreness were measured pretraining, post training, post treatment, and 24 hours post treatment. Changes in height of CMJ, sprint 20 m, blood lactate and change visual analogue scale for muscle soreness within passive recovery, cryotherapy, dan acupuncture were analyzed with independent t-test (p<0,05). CMJ was greatest in cryotherapy than acupuncture group and passive group immediately after recovery and 24 hours after recovery (p>0.05). Cryotherapy is faster recover in sprint 20 m immediately after recovery than passive recovery (p=0,000) and acupuncture has the same effect in sprint performance in 24 hours than passive recovery (p>0,05). However, there was no differences between cryotherapy and acupuncture (p=0,404). Furthermore, there was no differences on blood lactate immediately after recovery (p>0,05) between all type of recovery. There was an effect on muscle soreness in cryotherapy than acupuncture immediately after treatment, but in 24 hours after treatment, cryotherapy and acupuncture, both have no different respectively (p>0,05). The conclusion is cryotherapy has higher effects in accelerate recovery (power, speed, and muscle soreness) immediately and 24 hour after treatment, furthermore acupuncture just speed up recovery in speed performance 24 hours after treatment. Cryotherapy have better effect in physical performance recovery than acupuncture.